Data stewardship for discovery implementing fair principles - Mons, Barend (CRC Press, Taylor & Francis Group, 2018)
Data scientists and data experts in general will play a key role in the sciences in the decades to come. Yet there is not a comprehensive and flexible study book for the 'data steward' of today and the future. This practical book aims to remedy that. This book is written initially from a life-science perspective, but most approaches discussed and linked are of importance for all disciplines. The basic structure follows the so-called data stewardship cycle, from study design to interpretation and long term archiving and availability of data.